ORGANIZATION OF PRACTICAL TRAINING OF POLY-COMPETENT GRADUATES AT TECHNICAL UNIVERSITY - Igor O. Leushin; Irina V. Leushina (Высшее образование в России)
The article addresses the issues of practical training of technical university students. Inadmissibility of focusing on forming exceptionally professional competences of students to the detriment of general and cultural competences is shown. This negatively affects the quality of graduates' training and their competitive advantages on the market. The authors suggest students' practical training to be regarded as a complex of academic studies in the form of contact work of students and teachers and individual work of students comprising not only academic and work experience internship but also seminar type classes and course proj ects of all educational disciplines, not only those connected with specialty. Some difficulties concerning students' practical training organization and their causes are analyzed. The authors dwell on the innovative forms of organization proper "poly-competent" practical training for technical students. Special recommendations on the effective use of their potential are given.